ESVISIGN: Tanda Tangan Digital Sekolah Vokasi IPB - Walidatush Sholihah; Sofiyanti Indriasari; Inna Noviyanti; Anggi Mardiyono; Nur Aziezah (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2022)
All activities have been online since the Covid-19 pandemic broke out in Indonesia. IPB also supports government policy by partially locking down the campus area. Administrative activities are also in online mode. Online correspondence activities still require a signature as a form of validity and authentication of the letter. The scanned signature is different from the digital signature. Thus an application was made to create digital signatures. This application is named eSVi sign. This web-based application was made by using Prototype method. Prototype method consists of communication, planning and modeling quickly, making prototypes, submitting the system to users and feedback. This app uses a hash function with SHA256. Each signed document is assigned a hash value which is stored in storage. When the document is verified, the system will look for a hash value that matches the document in the database. The method to test this application was black box testing. This application can be accessed on the https://ipb.link/esvisign. This digital signature is only used within the College of Vocational Studies IPB University.